Pengaruh Jalur Pelaporan Anonim Terhadap Niat Whistleblowing Dengan Moderasi Religiusitas - Rosalyn Lakaba; David Adechandra Ashedica Pesudo (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
Whistleblowing is the exposure of individual or organization fraud committed by members of the organization related to fraud practices within the organization. Whistleblowing considered as an effective way to prevent and detect fraud. This study aims to examine the effect of anonymous report lines toward whistleblowing intentions with religiosity as a moderating variable. This research involves samples form a religion-based private university in Salatiga and a non-religious-based university located in Makassar because the author wants to know whether there is a difference or not. The result of this study showed that a religion-based university, a person’s intentions to do whistleblowing are influenced by the anonymous report lines. Otherwise, at a non-religious-based university, the anonymous report does not affect whistleblowing intentions. However, different from the prediction, this study found that religiosity cannot moderate the anonymous reporting line on whistleblowing intentions, both at religion-based and non-religious-based universities.